Upaya Peralihan Sertifikat Kepemilikan Tanah Apabila tidak Diketahui Keberadaan Penjualnya dalam Perspektif PTUN - Tasya Halimah Nia Purwanti; Amellia Intan Syavitri; Faisal Hasyim; Prabowo Abimanyu (Terang : Jurnal Kajian Ilmu Sosial, Politik dan Hukum, 2024)
The transfer of land ownership certificates is an important legal process in Indonesia's land system, regulated by various laws and regulations, such as the Basic Agrarian Law and its implementing regulations. The procedure for transferring ownership certificates begins with a legitimate sale and purchase transaction, followed by registration with the National Land Agency (BPN). However, in practice, obstacles often arise, one of which is when the seller's whereabouts are unknown, which can hinder the process of transferring land rights. In this situation, the buyer can take various legal actions, including filing a civil lawsuit in the District Court to obtain a court ruling confirming the legal transfer of rights, or submitting a request for a decree to the Administrative Court (PTUN) if BPN rejects the application for the transfer of land rights. The perspective of the PTUN legal procedure explains that the buyer can challenge the BPN decision if it is deemed contrary to the law or the principles of good governance (AUPB), with sufficient evidence to support their claim. In this case, PTUN plays a role in providing justice and legal certainty for the aggrieved party. Therefore, even when the seller’s whereabouts are unknown, through the appropriate procedures and legitimate legal actions, the buyer can still acquire ownership rights over the land purchased.